Odpowiedzi

2010-01-04T15:24:37+01:00
A) (-4) x (-8) : 2 - (-7) x 4 = 16 +28 = 44
b) 18 : (-2) : 3 + (-6)² : (-9) = -3 - 4 = -7
c) (10 - 14 - 24) : (-7) - (-15) : 3 = 6+ 5 = 11
d) 45 : (-9) + (-16) : (-4) - (-56) : 7 = -5 + 4 - 8 = -9
Najlepsza Odpowiedź!
2010-01-04T15:27:13+01:00
A )= 32 : 2 - (- 28) = 16 + 28 =44

b) = - 3 + (-4)= - 7

c) = 4 - (-5) = 4 + 5 = 9

d) = -5 + 4 - (-8) = -1 + 8 = 7
2010-01-04T15:28:57+01:00
A) (-4) x (-8) : 2 - (-7) x 4 = (-12)
b) 18 : (-2) : 3 + (-6)² : (-9) = (-7)
c) (10 - 14 - 24) : (-7) - (-15) : 3 = 9
d) 45 : (-9) + (-16) : (-4) - (-56) : 7 = 7